2015
DOI: 10.1074/jbc.m114.613810
|View full text |Cite
|
Sign up to set email alerts
|

Functional Amyloids Keep Quorum-sensing Molecules in Check

Abstract: Background:In biofilms, bacteria communicate via quorum-sensing (QS) molecules. Results:The specific binding affinity of QS molecules to a functional amyloid is determined. Conclusion: Functional amyloids can transiently bind and retain QS molecules. Significance: Functional amyloids are important for cell signaling within biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 74 publications
3
70
0
Order By: Relevance
“…Figure S4 shows the structural evolution of the LG21 peptide when it interacts with the Psl. It is observed that the middle residues (6)(7)(8)(9)(10)(11)(12)(13)(14) are the main contributors to the helical conformation. The reason could be that the presence of carbohydrate chain (Psl) in the solution decreases the polar nature of water to form hydrogen bonds with the middle residues and the increasing hydrophobic interactions within the peptide induces the helical structure, whereas the terminal residues still have a random-coil structure by being exposed to the aqueous solution.…”
Section: Molecular Dynamics (Md) Simulation Of Psl-lg21 Binding Modementioning
confidence: 99%
“…Figure S4 shows the structural evolution of the LG21 peptide when it interacts with the Psl. It is observed that the middle residues (6)(7)(8)(9)(10)(11)(12)(13)(14) are the main contributors to the helical conformation. The reason could be that the presence of carbohydrate chain (Psl) in the solution decreases the polar nature of water to form hydrogen bonds with the middle residues and the increasing hydrophobic interactions within the peptide induces the helical structure, whereas the terminal residues still have a random-coil structure by being exposed to the aqueous solution.…”
Section: Molecular Dynamics (Md) Simulation Of Psl-lg21 Binding Modementioning
confidence: 99%
“…Biofilm-associated bacteria, in particular, utilize amyloids as a building material to reinforce the EM and resist dispersion by chemical or mechanical agents [8, 11]. These fibrils may also promote antibiotic resistance and act as a reservoir for small molecules involved in quorum sensing [12, 13]. Amyloid fibrils polymerize in the absence of an energy source, so they serve as a metabolically advantageous molecular scaffold despite the limited resources of the EM environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fap fibrils have been shown to bind extracellular metabolites within the biofilm, such as quorum-sensing molecules and redox mediators, modulating their release and retention when required. This implies a potential new role for functional amyloids in molecular retention and indirect mediation of cell function (7,39,40) Again, genes encoding proteins with homology to the Fap systems are present within species belonging to the Beta-, Gamma-, and Deltaproteobacteria (38).…”
Section: Amyloid Structures With Dedicated Fiber Assembly Machinerymentioning
confidence: 99%